Reduction in the Diameter of Contact Holes with a High Anisotropy and Aspect Ratio. (1st January 2015) - Cho, Sung-Woon; Kim, Jun-Hyun; Kim, Sangin; Shin, Eun Woo; Kim, Chang-Koo
Abstract : SiO2 contact holes with a high anisotropy and aspect ratio were etched using an advanced cyclic etching (ACE) process to reduce the diameters of the contact holes. The ACE process consisted of the pre-deposition of a protection layer on the mask in a C4 F6 /CH2 F2 /Ar plasma and a subsequent cyclic process of alternating etching and deposition steps in C4 F6 /CH2 F2 /Ar/O2 and C4 F6 /CH2 F2 /Ar plasmas, respectively. The pre-deposition of the protection layer suppressed the mask-sidewall slope and mask faceting, thereby preventing the hole pattern from widening. An additional deposition step to the subsequent etching of the sample was introduced to maintain mask-sidewall protection and to deposit a passivation film on the sidewall of the contact hole. When the contact hole was etched using the conventional continuous etching process, its opening diameter increased by 22%, degree of bowing was 10 nm, and aspect ratio was 18. In contrast, by regulating the durations of the pre-deposition and alternating etching and deposition steps, the opening diameter was reduced by 26%, the degree of bowing was 2 nm, and the aspect ratio was 24 using the ACE process.